2023
DOI: 10.3389/fonc.2023.1090860
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ING3 expression in patients with cancer: A systematic review and meta-analysis

Abstract: BackgroundIt has been reported that ING3 inhibits the progression of various cancers. However, some studies have shown that it promotes the development of prostate cancer. The purpose of this study was to investigate whether ING3 expression is associated with the prognosis of patients with cancer.Materials and methodsPubMed, Cochrane Database, Embase, Medline, ScienceDirect, Scopus and Web of Science were searched until September 2022. The hazard ratio (HR)/odds ratio (OR) and 95% confidence interval (95% CI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Of the 97 known protein-coding genes at these loci, many of the genes located at, or spanning the peak QTL are known to be associated directly with cancer development, or with cancer associated pathways. For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 97 known protein-coding genes at these loci, many of the genes located at, or spanning the peak QTL are known to be associated directly with cancer development, or with cancer associated pathways. For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Past research demonstrated a close correlation between the occurrence of tumors and the immune status of the organism, with immune cells participating in various pathways involved in the initiation and progression of tumors. In previous studies on patients with malignant neoplasms such as lung cancer, esophageal cancer, colorectal cancer, and gastric cancer, researchers have detected decreased levels of CD3 + T cells, CD4 + T cells , NK cells, and CD4 + /CD8 + ratio in peripheral blood 4,[57][58][59][60] . The commonality among these findings reveals a prevalent state of immunosuppression in patients with malignant tumors, suggesting that changes in immune cell populations may be intimately associated with tumor burden in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: Esophageal cancer, Early detection, DNA methylation, Innovative approach, survival analysis, clinical implications Esophageal cancer is one of the foremost global causes of mortality [1]. There are two types of ESCA cancer: EAC (esophageal adenocarcinoma ( and squamous cell carcinoma (ESCC) [2]. EAC prevails in Western populations, whereas ESCC predominates in Asian nations, particularly China, with an incidence rate of 88.84 [3].…”
mentioning
confidence: 99%